The immediate effect of sildenafil on right ventricular function in patients with heart failure measured by cardiac magnetic resonance: a randomized control trial. - André Maurício S Fernandes; Agnes Carvalho Andrade; Natalia Duarte Barroso; Igor Carmo Borges; Dafne Carvalho-Andrade; Erenaldo S Rodrigues Junior; Libia Castro Guimarães; André Rodrigues Durães; Sirlene Mendes Borges; Roque Aras Junior (PLoS ONE)
Background Studies have demonstrated that phosphodiesterase 5 (PDE5) inhibition is associated with right ventricle (RV) functional improvement in patients with primary pulmonary hypertension. This study aims to demonstrate the immediate impact of Sildenafil, a PDE5 inhibitor, on RV function, measured by cardiovascular magnetic resonance (CMR), in patients with heart failure (HF). Methods We conducted a randomized double-blind controlled trial. Inclusion criteria diagnosis of HF functional class I-III; left ventricle ejection fraction < 35%. Patients underwent CMR evaluation and were then equally randomly assigned to either 50 mg of Sildenafil or Placebo groups. One hour following drug administration, they were submitted to a second scan examination. Results 26 patients were recruited from a tertiary reference center in Brazil and 13 were allocated to each study group. The median age was 61.5 years (50-66.5 years). Except for the increase in RV fractional area change following the administration of sildenafil (Sildenafil [before vs. after]: 34.3 [25.2-43.6]% vs. 42.9 [28.5-46.7]%, p = 0.04; Placebo [before vs. after]: 28.1 [9.2-34.8]% vs. 29.2 [22.5-38.8]%, p = 0.86), there was no statistically significant change in parameters. There was no improvement in left ventricular parameters or in the fractional area change of the pulmonary artery. Conclusion This study demonstrated that a single dose of Sildenafil did not significantly improve RV function as measured by the CMR. Trial registration ClinicalTrials.gov NCT01936350.